A novel role of Fas in delaying cellular senescence. Issue 2 (February 2023) - Saha, Chaitrali; Li, Jingyu; Sun, Xuerong; Liu, Xinguang; Huang, Gonghua
Abstract: Fas-mediated apoptosis is a major player of many physiological and pathological cellular processes. Fas-regulated immune regulation exhibits either the beneficial or the harmful effects which is associated with the onset or development of immune disorders. Alterations in apoptosis may contribute to age-associated changes. However, the role of apoptosis in the ageing process remains ambiguous. Here we demonstrated Fas signaling-mediated premature senescence in young mouse embryonic fibroblast (MEF) cells. Activated Fas signaling by agonist Jo-2 resulted in declined senescence in young and aged MEFs. Premature senescence induced the early activation of senescence markers, including the increase in the percentage of SA-β-galactosidase (SA-β-gal) cells, the induction of p53 phosphorylation, and the enhanced expression of p16 and p21 protein and elevated IL-6 pro-inflammatory cytokine in the absence of Fas. The elevated production of reactive oxygen species (ROS) in Fas-deficient MEFs was associated with dysfunctional mitochondria. Further, we determined that the known ROS scavenger NAC (N-acetyl-l -cysteine) could reverse the process of premature senescence in absence of Fas. Therefore, this study signifies a novel role of Fas in the control of cellular senescence. Graphical abstract: Image 1 Highlights: Absence of Fas signaling led to premature cellular senescence, which was significantly reduced by Fas agonist Jo-2 . Young Fas knock out (FasKO) MEF cells exhibit enhanced SA-β-gal activity, p16, p21, p53, pP38 and IGFBP5. Young FasKO cells display elevated inflammatory IL-6. Young FasKO MEF cells produced significantly higher ROS and defect in mitochondrial function. ROS scavenger NAC (N-acetyl-l -cysteine) could reverse the process of premature aging in absence of Fas.